Antimicrobial host defense peptides in an arteriviral infection: differential peptide expression and virus inactivation - Sang, Yongming; Ruchala, Piotr; Lehrer, Robert I.; Ross, Christopher R.; Rowland, Raymond R. R.; Blecha, Frank (My University, 2013)
Antimicrobial host defense peptides (AHDPs) are effective against a wide range of microbes, including viruses. The arteriviral infection caused by porcine reproductive and respiratory syndrome virus (PRRSV) is a devastating pandemic that causes the most economically significant disease of swine. We sought to determine if the expression of AHDPs was influenced by infection with PRRSV, and if porcine AHDPs have direct antiviral activity against PRRSV. Because pulmonary alveolar macrophages (PAMs) are primary targets of PRRSV infection, gene expression of porcine AHDPs was evaluated in lungs from fetal and 2-wk-old congenitally infected pigs. In PRRSV-positive lungs and PAMs, gene expression of most porcine AHDPs showed little upregulation. However, gene expression of porcine β-defensin-1 (pBD-1), pBD-4, pBD-104, pBD-123, and pBD-125 were downregulated more than threefold in 2-wk-old congenitally infected pig lungs. Incubation of PRRSV with pBD-3 or PG-4 significantly inhibited viral infectivity in MARC-145 cells. Using nine protegrin or protegrin-derived peptides, we determined that a cyclic analog of PG-4 increased anti-PRRSV activity, and that substitution of phenylalanine with valine eliminated most PG-4 antiviral activity. In PAMs, pBD-3 and PG-4 at 5–40 μg/mL consistently suppressed PRRSV titers. Collectively, these findings suggest a potential role for some porcine AHDPs as innate antiviral effectors in PRRSV infection. Moreover, modulation of porcine innate immune mechanisms with AHDPs may be one means of limiting the impact of this costly pandemic viral disease.
Keywords: Antimicrobial host defense peptides; Porcine reproductive and respiratory syndrome virus